C2C e-Marketplaces and How Their Micro-Segmentation Strategies Influence Their Customers - Castillo-Sotomayor, Sandra (2023)
The purpose of this study is to contribute to the literature, understanding how the micro-segmentation strategies developed by the C2C e-marketplaces influence customer satisfaction, brand loyalty, trust, and brand equity by proposing a PLS-SEM model with seven hypotheses. An online questionnaire was answered by a sample of 403 people. The results were edited, coded, transformed, and finally analysed with the software Smart- PLS 3.3.7. The results confirm that the reflective model shows good reliability and validity and that six of the seven were accepted. Furthermore, micro-segmentation mostly influences customer satisfaction, followed by brand equity and trust. On the other hand, the results confirm that, apparently, customer satisfaction does not impact brand loyalty, and micro-segmentation is the more significant construct in reaching brand loyalty in the C2C e-marketplaces. It is worth noting that this research contributes to knowledge about two issues unexplored by the academia, micro-segmentation and the C2C e-marketplaces. Dataset: https://data.mendeley.com/datasets/zzx5kw6cy9/1 Dataset License: CC BY 4.0.